Effect of a lactate-guided conditioning program on heart rate variability obtained using 24-Holter electrocardiography in Beagle dogs - Restan, Alejandro Z. [UNESP]; Camacho, Aparecido A. [UNESP]; Cerqueira, Juliana A. [UNESP]; Zacché, Evandro [UNESP]; Kirnew, Murillo D. [UNESP]; Loureiro, Bruna A.; Silva, Samara B. [UNESP]; Moranza, Henriette G. [UNESP]; Ferraz, Guilherme C. [UNESP] (Public Library of Science (PLoS), 2020)
The dogs' responses to training exercise are seldom monitored using physiological variables, and cardiac autonomic regulation (CAR) is a relevant determinant of endurance-training adaptation. There are studies in the literature establishing that regular exercise could interfere with CAR in dogs, measured by heart rate and vagal-derived indexes of heart-rate-variability (HRV). However, few studies were found using a prescribed training program based on the lactate threshold (LT) to determine HRV by a 24-h Holter analysis. The purpose of this study was to test whether an endurance-training program (ETP) guided individually by LT raises time-domain measures of HRV in healthy Beagle dogs. Twenty dogs were assigned to two groups: control (C) and trained (T). The dogs from group T underwent an incremental exercise test (IET) to determine their LT. Both LT and velocity corresponding to the LT (VLT) was determined by visual inspection. T group performed an eight-week endurance-training program consisting of treadmill runs set to 70–80% of the VLT. Next, dogs from the group T have submitted to IET again. The maximal velocities (Vmax) at which achieved by the trained dogs in both IETs were determined. The group S did not undergo IETs or ETP. HRV was determined by the 24-hour-Holter at rest, before and on the 2°, 4°, 6° and 8° training weeks. To examine the HR impact on HRV, standard HRV variables were normalized to prevailing HR. VLT and Vmax rose in group T, indicating an improvement of dogs' aerobic and anaerobic capacity. The normalized standard HRV indexes were relatively attenuated since these variables had a reduction in the degree of correlation concerning an average HR. The ETP resulted in decreased resting heart rate and increased time-domain indices, highlighting the log-transformed square root of the mean sum of the squared differences between R–R intervals (Ln rMSSD). The lactate-guided endurance-training program could lead to better parasympathetic cardiac modulation in Beagle dogs.